Nickel tolerance of serpentine and non-serpentine Knautia arvensis plants as affected by arbuscular mycorrhizal symbiosis - Doubková, Pavla; Sudová, Radka (Mycorrhiza, 2014)
Serpentine soils have naturally elevated concentrations of certain heavy metals, including nickel. This study addressed the role of plant origin (serpentine vs. non-serpentine) and symbiosis with arbuscular mycorrhizal fungi (AMF) in plant Ni tolerance. A semi-hydroponic experiment involving three levels of Ni and serpentine and non-serpentine AMF isolates and populations of a model plant species (Knautia arvensis) revealed considerable negative effects of elevated Ni availability on both plant and fungal performance. Plant growth response to Ni was independent of edaphic origin; however, higher Ni tolerance of serpentine plants was indicated by a smaller decline in the concentrations of photosynthetic pigments and restricted root-to-shoot Ni translocation. Serpentine plants also retained relatively more Mg in their roots, resulting in a higher shoot Ca/Mg ratio. AMF inoculation, especially with the non-serpentine isolate, further aggravated Ni toxicity to host plants. Therefore, AMF do not appear to be involved in Ni tolerance of serpentine K. arvensis plants.
Keywords: nikl; mykorhiza; Fungi; Plants; rostliny; houby; Mycorrhizae; Symbiosis; Nickel; Dipsacaceae; symbióza